2004
DOI: 10.1002/cncr.20556
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment probability model for predicting outcome after intraarterial chemoradiation for advanced head and neck carcinoma

Abstract: BACKGROUNDConcurrent chemoradiation is being used increasingly to treat patients with advanced‐stage head and neck carcinoma. In the current study, a clinical nomogram was developed to predict local control and overall survival rates for individual patients who will undergo chemoradiation.METHODSNinety‐two consecutive patients with UICC TNM Stage III/IV squamous cell carcinoma of the oral cavity, oropharynx, hypopharynx, and supraglottic larynx were treated with selective‐targeted chemoradiation (acronym: RADP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 44 publications
1
36
0
1
Order By: Relevance
“…Reported risk factors for distant metastasis included N stage (p = .02), primary tumor in the hypopharynx (p = .01), lower neck involvement (p = .002), number of neck levels involved (p = .001), and bilateral nodal disease (p = .02). Similar results were described by van den Broek et al [57] Alkureishi, de Bree, Ross 475 www.TheOncologist.com in a series of 92 patients, with tumor volume (p = .003), lowest involved neck level (p = .007), pretreatment weight loss >10% (p = .02), and associated comorbidity (p = .01) all found to significantly influence survival following RAD-PLAT treatment.…”
Section: Predictors Of Successsupporting
confidence: 88%
See 1 more Smart Citation
“…Reported risk factors for distant metastasis included N stage (p = .02), primary tumor in the hypopharynx (p = .01), lower neck involvement (p = .002), number of neck levels involved (p = .001), and bilateral nodal disease (p = .02). Similar results were described by van den Broek et al [57] Alkureishi, de Bree, Ross 475 www.TheOncologist.com in a series of 92 patients, with tumor volume (p = .003), lowest involved neck level (p = .007), pretreatment weight loss >10% (p = .02), and associated comorbidity (p = .01) all found to significantly influence survival following RAD-PLAT treatment.…”
Section: Predictors Of Successsupporting
confidence: 88%
“…A reliable pretreatment probability model for predicting outcome after RAD-PLAT is needed to select patients with resectable tumors who are likely to benefit from chemoradiation. If RAD-PLAT is unlikely to cure patients with resectable tumors, these patients should instead be treated with primary surgery [57].…”
Section: Surgery After Chemoradiation Treatmentmentioning
confidence: 99%
“…Since tumor volume is a strong predictor of outcome 8,9 in advanced head and neck squamous cell carcinomas, we looked for Intermediate group. LC, local control; OS, overall survival; nm, not mentioned; u, univariable analysis; m, multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with advanced head and neck cancer it has been demonstrated that T and N stage do not have sufficient predictive value. 8,9 Tumor volume has been shown to be the most predictive factor for LC. [8][9][10][11][12] For OS, tumor volume, comorbidity, lowest involved neck level and pretreatment weight loss have been found to be prognostic.…”
mentioning
confidence: 99%
“…10,11 In addition, patients with critical weight loss reported lower quality-of-life scores and poorer treatment tolerance. 7,[12][13][14] Several studies have shown nutritional interventions in HN cancer patients to have a positive impact on their nutritional status, quality of life, and treatment compliance.…”
mentioning
confidence: 99%